The Implementation of Virtual Laboratories in Hormone System Instruction to Improve Students’ Digital Habits of Mind - Lyra Azka Amalia; Hizqiyah, Ida Yayu Nurul; Aryanti, Fitri (Jurnal Report of Biological Education, 2025)
Biology education in the 21st century demands that students think critically, adaptively, and be able to solve problems. These skills are reflected in the concept of Digital Habits of Mind (Digital HoM). The endocrine system topic, particularly blood glucose regulation, remains a challenging subject for students. Based on interviews with biology teachers, students experience difficulties in understanding the mechanism of insulin function. On the other hand, Digital HoM skills have not been explicitly facilitated in learning, despite their importance in facing educational challenges in the digital era. This study aims to develop students’ Digital HoM skills through the use of a virtual laboratory on the topic of the endocrine system. Method: The method used is a quasi-experimental design with a one-group pretest-posttest involving 42 eleventh-grade students selected through purposive sampling. The main data were obtained from observation sheets based on Hizqiyah’s Digital HoM framework, and supporting data were collected through pretest and posttest results. Results The findings indicate that the virtual laboratory has a positive effect on both Digital HoM skills and students’ conceptual understanding. Conclusion:  Although no statistical correlation was found between the two, the integration of the virtual laboratory was shown to strengthen both aspects concurrently. Keywords : Digital Habits of Mind; Virtual Laboratory; Hormonal System